Borehole inclination effects to the wellbore stability and sand production - Samsuri, Ariffin; S., Surej Kumar; S., Sharin; A., Tzarina; O., Norjusni (1995)
The paper presents the result of a laboratory study of the wellbore stability and sand particles produced from unstable perforated wellbore. Section of a perforated wellbore were generated and exposed to various loads and conclusions were drawn with respect to the failure load and sand particles produced during the loading process. The result shows that the perforated wellbore may fail during the creation process and sand particles were produced, depending on the borehole inclination angle, phasing angle and perforation pattern. The sand particles produced were found by sieve analysis to be oversized 500 micron. Generally, stable perforated wellbore produced less sand particles, therefore minimizing the rig problem i.e. deformation of formation and sand production.